Identification of Vibrio spp. in Spiny Lobster (Panulirus homarus) from Natural Catch and Culture In Batu Bangka Village, Sumbawa - Elviantari, Adelia; Adi Suriyadin; Abdurachman, Muhammad Haikal (Department of Aquaculture, 2024)
Spiny lobster (Panulirus homarus) is a fishery commodity with high economic value. The classic problem that has not been resolved so far is the low survival rate of around 20-30% and an average growth rate of 180-230 grams. This can be influenced by nutritional factors, environment, stress and pathogen infection. This study aimed to identify pathogenic bacteria found in wild caught lobsters (Labangka) and cultivated lobsters (Bungin Island). The stages of this research began with taking samples in the field, followed by isolation and purification of bacteria (tail organs, gills, and hepatopancreas), morphological characteristics, and physiological tests of bacterial isolates. From the results of the study, it was found that the isolates grown on TSA media, showed a higher diversity of bacteria in natural lobsters compared to cultivated lobsters, this is what makes natural lobsters have a high survival rate because the diversity of microflora forms a symbiotic mutualism. Meanwhile, if we look at the diversity of pathogenic bacteria (Vibrio spp.), namely isolates grown on TCBS media, it shows that cultivated lobsters have more diverse pathogenic bacteria, namely three types of Vibrio (V. alginilyticus, V. Harvey and V. Parahemolyticus) are indicated, only natural lobsters identified V. alginilyticus.